2007
DOI: 10.1111/j.1467-9221.2007.00589.x
|View full text |Cite
|
Sign up to set email alerts
|

Expertise, Evaluative Motivation, and the Structure of Citizens’ Ideological Commitments

Abstract: Political psychologists have engaged in a number of critical debates about the underlying structure of citizens' ideological commitments. The most prominent of these debates have focused on whether members of the mass public use the higher-order distinction between "conservatism" and "liberalism" to structure their opinions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Moreover, despite the fact that at least two-thirds of adults identify themselves as liberals or conservatives, only a minority of citizens can accurately think about politics in the abstract ideological language of liberalism versus conservatism (Campbell et al, 1960;Delli Carpini & Keeter, 1996;Erikson & Tedin, 2003;Stimson, 2004; but see Jost, 2006, for another perspective on being ''ideological''). However, research also suggests that political elites and members of the mass public with high levels of political expertise-who are more likely to have learned the ideological language elites use to discuss politics-are more likely to correctly understand and use ideologies to structure their attitudes (resulting in higher levels of ideological consistency among attitudes, a stronger tendency to conceptualize politics in ideological terms, and so on; see Campbell et al, 1960;Converse, 1964Converse, , 2000Delli Carpini & Keeter, 1996;Erikson & Tedin, 2003;Federico, 2007;Federico & Schneider, 2007;Judd & Krosnick, 1989;Kinder, 2006;Lavine, Thomsen, & Gonzales, 1997;Layman & Carsey, 2002;Zaller, 1992). Thus, although various prepolitical variables may play a role in citizens' ideological affinities, it is also clear that citizens vary widely in the extent to which they understand the ideological attitude systems they have to choose from in the first place.…”
Section: Political Expertise and The Worldview-ideology Connectionmentioning
confidence: 97%
“…Moreover, despite the fact that at least two-thirds of adults identify themselves as liberals or conservatives, only a minority of citizens can accurately think about politics in the abstract ideological language of liberalism versus conservatism (Campbell et al, 1960;Delli Carpini & Keeter, 1996;Erikson & Tedin, 2003;Stimson, 2004; but see Jost, 2006, for another perspective on being ''ideological''). However, research also suggests that political elites and members of the mass public with high levels of political expertise-who are more likely to have learned the ideological language elites use to discuss politics-are more likely to correctly understand and use ideologies to structure their attitudes (resulting in higher levels of ideological consistency among attitudes, a stronger tendency to conceptualize politics in ideological terms, and so on; see Campbell et al, 1960;Converse, 1964Converse, , 2000Delli Carpini & Keeter, 1996;Erikson & Tedin, 2003;Federico, 2007;Federico & Schneider, 2007;Judd & Krosnick, 1989;Kinder, 2006;Lavine, Thomsen, & Gonzales, 1997;Layman & Carsey, 2002;Zaller, 1992). Thus, although various prepolitical variables may play a role in citizens' ideological affinities, it is also clear that citizens vary widely in the extent to which they understand the ideological attitude systems they have to choose from in the first place.…”
Section: Political Expertise and The Worldview-ideology Connectionmentioning
confidence: 97%
“…It is important to note that although we expect that some individuals have relatively incompatible attitudes toward peace and war, for some individuals the attitudes can be relatively compatible (the warlike peaceniks would care about both, and the unconcerned do not give much value to either). In a similar way, researchers showed that although conservatism and liberalism tend to be generally opposed in people's minds, there are certain individuals who may have positive attitudes toward both (see Federico, ; Sidanius & Duffy, ).…”
mentioning
confidence: 93%
“…unconcerned do not give much value to either). In a similar way, researchers showed that although conservatism and liberalism tend to be generally opposed in people's minds, there are certain individuals who may have positive attitudes toward both (see Federico, 2007;Sidanius & Duffy, 1988).…”
mentioning
confidence: 94%
“…As advanced by Downs (), ideological poles provide an informational shortcut useful to make low‐cost political judgments (Grofman, ; Popkin, ). Some scholarly literature believes that the lack of issue consistency may impose excessive informational demands on voters (Federico, ), which could put them apart from politics, and ideologies may help them to simplify the complexity of politics by reducing the dimensions of conflict from many to few (Jost, Federico, and Napier, ). I call low‐sophisticated citizens with high ideological levels passive ideological voters .…”
Section: Theoretical Backgroundmentioning
confidence: 99%